Extreme temperature effects on the ultrastructure of mitochondria of mesophyll cells in Triticum spelta leaves - Babenko, L.M.; Vodka, M.V.; Akimov, Yu.N.; Babenko, A.V.; Kosakivska, I.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
The effects of high (40 °C, 2 h) and positive low (4 °C, 2 h) temperatures on the ultrastructure of mitochon d ria of the mesophyll cells in Triticum spelta L. leaves are analyzed. Control plants are shown to have round mitochondria and are characterized by an electrondense matrix and the presence of numerous developed laminar cristae. Under conditions of hyperthermia, mitochondria were "swollen", the crystal membranes became less contrast, the electron density of the matrix decreased, and the number of mitochondria increased. With hypothermia up to 40 %, the mitochondria retained a rounded shape, and organelles of "lenticular", "dumbbell", and "cupshaped" forms appeared. The number of mitochondria in the diametrical section of a cell did not change. Changing in the shape of the organelles led to an increase in the area of their surface, which probably promotes the metabolites exchange with cytoplasm and thus contributes to the increased stress tolerance.